2016
DOI: 10.1089/ten.tea.2016.0103
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Environment Sustains Morphological Heterogeneity and Promotes Phenotypic Progression During Astrocyte Development

Abstract: Astrocytes are critical for coordinating normal brain function by regulating brain metabolic homeostasis, synaptogenesis and neurotransmission, and blood-brain barrier permeability and maintenance. Dysregulation of normal astrocyte ontogeny contributes to neurodevelopmental and neurodegenerative disorders, epilepsies, and adverse responses to injury. To achieve these multiple essential roles, astrocyte phenotypes are regionally, morphologically, and functionally heterogeneous. Therefore, the best regenerative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 112 publications
6
45
0
Order By: Relevance
“…As a complement to in vivo experiments, in vitro studies offer great potential in this regard; however, previous studies of ONH astrocyte mechanobiology have used monolayer-based approaches, which do not accurately represent the physiological environment of the ONH. Notably, monolayer culture induces an artificially reactive phenotype in cultured astrocytes,4,14 making it difficult to interpret the effect of biomechanical strain in such studies.…”
mentioning
confidence: 99%
“…As a complement to in vivo experiments, in vitro studies offer great potential in this regard; however, previous studies of ONH astrocyte mechanobiology have used monolayer-based approaches, which do not accurately represent the physiological environment of the ONH. Notably, monolayer culture induces an artificially reactive phenotype in cultured astrocytes,4,14 making it difficult to interpret the effect of biomechanical strain in such studies.…”
mentioning
confidence: 99%
“…In a broad range of contexts, the epigenetics and morphology of cells in vivo can be well-approximated in 3D hydrogel cultures. Though simple hydrogels cannot recapitulate the entire complexity of in vivo tissues, they do provide strikingly similar results compared to 2D cell culture [2627, 29]. Depending on the application, the optimal physiochemical properties of the hydrogel model will vary.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we cannot rule out that the attenuation of Aβ toxicity in hydrogels is influenced by confinement of the cells themselves or effects from the stiffness of the cellular microenvironment. However, we hold that these possibilities are unlikely given the evidence that 3D culture allows cells to more closely mimic in vivo phenotypes vs. 2D culture [2627, 29]. More importantly, we reported in 2002 that agarose itself does not confer a protective effect against the cytotoxicity of the Aβ 1-40 amino acid sequence [43].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing appreciation that cells grown in vitro , on rigid polystyrene tissue culture surfaces, behave very differently than cells in vivo , and that the stiffness of the surface upon which cells are grown can have profound epigenetic effects on cells that influence their phenotype [80, 81]. In addition, many investigators have observed that morphologies of neuronal cells are strikingly more similar to those expressed in vivo in 3D vs. 2D culture [22, 23, 82, 83]. Thus, the use of 3D cell culture models for AD drug development may lead to a more positive correlation between successes in vitro and successes in clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We supposed that this effect could be due to one of two effects, either (1) the 3D environment altered the phenotype of the PC12 cells, making them less susceptible to Aβ, or (2) the 3D environment altered the aggregation of Aβ. Given that PC12 cells and other neuron-like cells take on a phenotype more closely associated with an in vivo neuron in 3D [22, 23, 84], we assumed that our first hypothesis was less probable. Therefore, in this work, we set out to investigate how the 3D collagen hydrogel environment affects Aβ structure and aggregation.…”
Section: Discussionmentioning
confidence: 99%